ANALISIS ETIKA BISNIS ISLAM DALAM MENINGKATKAN KEPUASAN PELANGGAN (STUDI USAHA BENGKEL MOTOR 38B LAMPUNG TIMUR) - Lily Cahyanti; Dewi Asiyatus Shofuroh; Lilis Renfiana (EKSYA : Jurnal Ekonomi Syariah, 2023)
The research aims to know the ethics of the Islamic business in increasing customer satisfaction with the 38b east lampung auto shop and to know what principles and dimensions could increase customer satisfaction.Qualitative is the method used in this research. Using purposive sampling data retrieval techniques and sample retrieval techniques sampling insidental which are then followed up with interviews, documentation and observations. Based on the results of the research and discussion in this case have found two suitable Abe Motor workshops and the Buntung Motor workshop.It can be seen that the quality of Abe's auto service in increasing customer satisfaction is 100% in transactional, 70% for refrenction and 30% for prefencials. Then for the buntung motor workshops it can be seen that in increasing satisfaction there is 100% for transactional, 40% for refrenalization and 0% for preferential. Selfies judging from the ethics of the Islamic business Abe motor, Abe meets the four Islamic principles of justice/balance, free will, responsibility and ihsan, and does not fulfill a single ethical principle of the Islamic business which is tauhid unity. Whereas buntung motor workshop fulfills only three business ethics principles of free will, responsibility and ihsan, not the two ethics of unified business /tauhid and justice/balance.